Analisis Green Accounting, Csr, dan Profitabilitas Terhadap Nilai Perusahaan Manufaktur - Ardiansyah, Richard Danang; Widoretno, Astrini Aning (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test and analyze the influence of green accounting, CSR, and profitability on the value of manufacturing companies listed on the Indonesia Stock Exchange during 2021-2022. Sampling using the purposive sampling method resulted in one hundred and forty-four companies. This research is quantitative research that uses secondary data. The data analysis techniques used are descriptive statistical analysis and multiple regression analysis. This research shows that green accounting has no effect, while CSR and profitability affect company value. Furthermore, Green Accounting, CSR, and Profitability simultaneously influence company value.